NANOCREAM FOUNDATION FORMULATION LOADED WITH ETHYL ACETATE FRACTION FROM MELASTOMA MALABATHRICUM l. - PRATIWI, LIZA; SARI, RAFIKA; APRIDAMAYANTI, PRATIWI (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to create a nanocream formula of the ethyl acetate fraction of Melastoma malabathricum using Design-Expert software. The objective was to obtain an optimal nanocream formula, analyze its characteristics, test its real-time stability, and measure its free radical scavenging ability using the DPPH method. Methods: The study began by manufacturing 70% ethanol extract from Melastoma malabathricum leaves and fractionating it with ethyl acetate to obtain the desired fraction. The fraction was then used to create a nanocream using cetyl alcohol, liquid paraffin, and propylene glycol in a ratio of 5:5:15. The optimal formula was tested for real-time stability and antioxidant effectiveness using the DPPH method. Results: Based on the results of the study, the optimal formula of the nanocream foundation preparation of the ethyl acetate fraction of Melastoma malabathricum was a combination of cetyl alcohol, liquid paraffin and propylene glycol in a ratio of 5:5:15. The results showed that the optimal nanocream formula had a pH value of 6.1±0.36, a spreadability of 6.57 cm ±0.06, and an adhesion of 22.20 minute±0.03. The particle size was determined to be 47 nm±0.78. The optimal formula also showed practical free radical scavenging ability, with an IC50 value of 556,29±0,155. The nanocream was stable for 28 d of real-time testing, and the honey extract remained stable during freeze-thaw. Conclusion: In conclusion, using the design-expert software, the study successfully created a nanocream formula from the ethyl acetate fraction of Melastoma malabathricum (NFMM). The resulting nanocream had physical characteristics that met the requirements for pH, spreadability, adhesion, and particle size. It was stable for 28 d of real-time testing and showed antioxidant activity when tested with the DPPH method.